#TITLE_ALTERNATIVE# - ANDINI (NIM: 10511071 ), SHITA
Heavy metals are metals with high atomic weight. Heavy metals in low levels, generally are already toxic to plants and animals, including human. The influx of heavy metal wastes into the sea waters have caused pollution against the water. Therefore, the research studied about heavy metals in sea waters of Pantai Gebang 1, Pantai Gebang 2 and Pelabuhan Cirebon in the coastal area of Cirebon. It also carried out research on existence of phenol compounds, 2,4-dinitrophenol, and 4-aminophenol and determine the matrix effect of the sea water sample towards the analysis of the compounds. The phenol compound and its derivatives is a pollutant commonly found in the waters of the sea, which is derived from oil spills or dumping waste oil into the sea that has high toxicity towards water organisms. The research of metal content analysis i.e. Cu, Fe, Cd, and Zn was performed using atomic absorption spectrophotometer (AAS). The results showed for sea water sample of Pantai Gebang 1 contains metals Cu, Fe, Cd, and Zn, in a row 0.22 ppm, 0.83 ppm, 0.13 ppm, and 0.20 ppm. Pantai Gebang 2 contains metals Cu, Fe, Cd, and Zn, in a row 0.12 ppm, 1.06 ppm, 0.12 ppm, and 0.16 ppm, while Pelabuhan Cirebon contains metals Cu, Fe, Cd, and Zn in a row 0.10 ppm, 1.33 ppm, 0.15 ppm, and 0.13 ppm. Analysis of phenolic compounds, 2.4-dinitrophenol, and 4-aminophenol have been done using High Performance Liquid Chromatography (HPLC) reversed-phase and solid phase extraction (SPE). The selection of the wavelength in the analysis are based on the HPLC respectively the maximum absorption of phenol compounds, 2.4-dinitrophenol, and 4-aminophenol that are retrieved from the maximum absorption test using a UV Spectrophotometer. From the results of the study, all of the samples showed peaks at chromatogram, on the sample of Pantai Gebang 1 showed peaks at the retention time of 1.247 minutes and 2.630 minutes, Pantai Gebang 2 showed peaks at the retention time of 1.250 minutes and 2.645 minutes, and Pelabuhan Cirebon showed a peak at the retention time of 1.257 minutes and 2.630 minutes which is the possibility of compounds 2.4-dinitrofenol and phenol. The results showed the matrix effect of sea water sample does not interfere in the determination of phenolic compounds, 2.4-dinitrophenol, and 4-aminophenol. Supporting parameters in this research in the temperature form of Pantai Gebang 1 was 26.2 , Pantai Gebang 2 was 26.2 , and Pelabuhan Cirebon was 26.6 , pH of Pantai Gebang 1 was 8.85, Pantai Gebang 2 was is 8.10, and Pelabuhan Cirebon was 8.02. And characterization using infrared spectrum (IR) of all three samples in order to obtain the dominant functional clusters that always exist at every location of the sea water sampling, clusters of them include N-H, O-H, C-H, Si-OR, C-halide and Si-O-Al or Si-O-Mg.